1973
DOI: 10.1139/b73-287
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of peroxidase activity by gibberellin and auxin in pea stem segments

Abstract: Peroxidase activity in excised stem segments of Pisum sativum L. cv. Progress No. 9 increases linearly during incubation in buffered medium. Gibberellic acid (GA) causes a slight reduction in activity whereas indoleacetic acid (IAA) treatment completely prevents this rise. Excision produces two new cathodic isoperoxidases near the cut ends. Their appearance is prevented by cycloheximide, actinomycin D, and IAA; G A enhances this IAA-induced repression. GA alone stimulates one of the isozymes but does not affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1974
1974
1999
1999

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The reduction in peroxidase activity by exogenously applied IAA has been reported in several plant systems (Gordon and Henderson 1973, Morrow and Jones 1986, Ockerse et al 1965, Ockerse and Mumford 1973, Ros Barceló et al 1989), but only a few reports describe the effect of this auxin on peroxidases from the cell walls (Morrow andJones 1986, Ros Barceló et al 1989). In pea internode sections, intercellular peroxidase activity was decreased by IAA treatment, an effect that correlated inversely with the elongation rate (Morrow and Jones 1986), and application of IAA or 2,4 dichlorophenoxiacetic acid to exponentially growing lupin hypocotyls promoted a reduction in the level of free intercellular peroxidases (Ros Barceló et al 1989).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The reduction in peroxidase activity by exogenously applied IAA has been reported in several plant systems (Gordon and Henderson 1973, Morrow and Jones 1986, Ockerse et al 1965, Ockerse and Mumford 1973, Ros Barceló et al 1989), but only a few reports describe the effect of this auxin on peroxidases from the cell walls (Morrow andJones 1986, Ros Barceló et al 1989). In pea internode sections, intercellular peroxidase activity was decreased by IAA treatment, an effect that correlated inversely with the elongation rate (Morrow and Jones 1986), and application of IAA or 2,4 dichlorophenoxiacetic acid to exponentially growing lupin hypocotyls promoted a reduction in the level of free intercellular peroxidases (Ros Barceló et al 1989).…”
Section: Resultsmentioning
confidence: 99%
“…Catabolism of IAA through oxidation has been demonstrated to be catalyzed by peroxidases in active growing tissues (Gordon and Henderson 1973, Ockerse and Mumford 1973). Several studies indicated that IAA decreased peroxidase activity in plant tissues in which this auxin induces cell elongation (Morrow and Jones 1986, Ockerse and Mumford 1973, Ros Barceló et al 1989).…”
mentioning
confidence: 99%
See 3 more Smart Citations